"Anticonvulsant Action" of Vitamin D in Epileptic Patients? A Controlled Pilot Study. Issue 5913 (4th May 1974) - Christiansen, Claus; Rødbro, Paul; Sjö, Ole
Abstract : The frequency of epileptic seizures was observed in a controlled therapeutic trial on 23 epileptic inpatients before and after treatment with vitamin D2 or placebo in addition to anticonvulsant drugs. The number of seizures was reduced during treatment with vitamin D2 but not with placebo. The effect was unrelated to changes in serum calcium or magnesium. The results may support the concept that epileptics should be treated prophylactically with vitamin D.